A two-stage supply chain in a price-and-time dependent market with demand leakage and producing curve. (3rd April 2019) - Wang, Kuo-Hsien; Huang, Yuan-Chih; Tung, Che-Tsung
ABSTRACT: We consider a decentralized supply chain that a manufacturer wholesales a product to a retailer who sells the product on a price-and-time dependent market with a two-stage strategy over the selling period, including a retail store in the first stage and a retail store and an online store in the second stage. We assume the manufacturer follows a producing curve to manufacture the product and set the two stages' wholesale prices. Demand leakage from the retail store to the online store is considered. Our supply chain is developed to explore how a volatile online market will impact the chain's performances. Numerical examples are conducted to identify the double marginalization effect that both members will never agree on the same timing to practice the second stage, which seriously undermines the manufacturer's profit; especially in a high price- or time-sensitive online market.